Microwave characteristics of sol-gel based Ag-doped (Ba 0.6Sr0.4)TiO3 thin films (2014)
Dielectric Ba0.6Sr0.4TiO3 (BST) thin films with a different concentration of Ag-dopant of 0.5, 1, 1.5, 2, 3, and 5 mol % have been prepared using an alkoxide-based sol-gel method on a Pt(111)/TiO 2/SiO2/Si substrate and their surface morphology and crystallinity have been examined using scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis, respectively. An on-chip metal-insulator-metal capacitor has been fabricated with the prepared thin film ferroelectric sample. Concentric coplanar electrodes are used for high frequency electrical characterization with a vector network analyzer and a probe station. The SEM images show that increasing Ag doping concentration leads to a decrease in grain size. XRD reveals that the fabricated films show good BST crystallinity for all the concentration while a doping concentration of 5 mol % starts to show an Ag peak, implying a metallic phase. Improved microwave dielectric loss properties of the BST thin films are observed in a low Ag doping level. Especially, BST with an Ag doping concentration of 1 mol % shows the best properties with a dielectric constant of 269.3, a quality factor of 48.1, a tunability at the electric field of 100 kV/cm of 41.2 %, a leakage-current density of 1.045 × 10- 7A/cm2 at an electric field of 100 kV/cm and a figure of merit (defined by tunability (%) divided by tan δ (%)) of 19.59 under a dc bias voltage of 10 V at 1 GHz. © 2014 Elsevier B.V. All rights reserved.